Neuromodulation-induced prehabilitation to leverage neuroplasticity before brain tumor surgery: a single-cohort feasibility trial protocol - Boccuni, Leonardo; Abellaneda-Pérez, Kilian; Martín-Fernández, Jesús; Leno-Colorado, David; Roca-Ventura, Alba; Prats Bisbe, Alba; Buloz-Osorio, Edgar Antonio; Bartrés-Faz, David; Bargalló, Nuria; Cabello-Toscano, María; Pariente, José Carlos; Muñoz-Moreno, Emma; et al. (Frontiers in Neurology, 2023)
Introduction. Neurosurgery for brain tumours needs to find a complex balance between effective removal of targeted tissue and preservation of surrounding brain areas. Neuromodulation-Induced Cortical Prehabilitation (NICP) is a promising strategy that combines temporary inhibition of critical areas (virtual lesion) with intensive behavioural training to foster the activation of alternative brain resources; by progressively reducing the functional relevance of targeted areas, the goal is to facilitate resection with reduced risks of neurological sequelae. However, it is still unclear which modality (invasive versus non-invasive neuromodulation) and volume of therapy (behavioural training) may be optimal in terms of feasibility and efficacy.Patients undertake between 10 to 20 daily sessions consisting of neuromodulation coupled with intensive task-training, individualized based on target site and neurological functions at risk of being compromised. The primary outcome of the proposed pilot, single-cohort trial is to investigate the feasibility and potential effectiveness of a non-invasive NICP protocol on neuroplasticity and post-surgical outcomes. Secondary outcomes investigating longitudinal changes (neuroimaging, neurophysiology and clinical) are measured pre-NICP, post-NICP, and post-surgery.Ethics and dissemination. Ethical approval was obtained from the Research Ethical Committee of Fundació Unió Catalana d'Hospitals (approval number: CEI 21/65, version 1, 13/07/2021). The results of the study will be submitted to a peer reviewed journal and presented at scientific congresses.Registration details. ClinicalTrials.gov Identifier NCT05844605.